The role of auxin and sugar signaling in dominance inhibition of inflorescence growth by fruit load. Issue 3 (22nd May 2021) - Goetz, Marc; Rabinovich, Maia; Smith, Harley M
Abstract: Dominance inhibition of shoot growth by fruit load is a major factor that regulates shoot architecture and limits yield in agriculture and horticulture crops. In annual plants, the inhibition of inflorescence growth by fruit load occurs at a late stage of inflorescence development termed the end of flowering transition. Physiological studies show this transition is mediated by production and export of auxin from developing fruits in close proximity to the inflorescence apex. In the meristem, cessation of inflorescence growth is controlled in part by the age-dependent pathway, which regulates the timing of arrest. Here, we show the end of flowering transition is a two-step process in Arabidopsis ( Arabidopsis thaliana ). The first stage is characterized by a cessation of inflorescence growth, while immature fruit continues to develop. At this stage, dominance inhibition of inflorescence growth by fruit load is associated with a selective dampening of auxin transport in the apical region of the stem. Subsequently, an increase in auxin response in the vascular tissues of the apical stem where developing fruits are attached marks the second stage for the end of flowering transition. Similar to the vegetative and floral transition, the end of flowering transition is associated with a change in sugar signaling and metabolism in the inflorescence apex. Taken together, our results suggest that during the end of flowering transition, dominance inhibition of inflorescence shoot growth by fruit load is mediated by auxin and sugar signaling. Abstract : Dominance inhibition of inflorescence shoot growth by fruit load involves auxin and sugar signaling during the end of flowering transition.